Development of Learning Management System-Based Teaching Materials to Increase Students' Learning Independence - Tri Yunita; Alexon Alexon; Eko Risdianto (Indonesian Journal of E-learning and Multimedia (IJOEM), 2023)
This research aims to develop appropriate teaching materials for the Vocational Fundamentals subject in Class X using the Learning Management System (LMS), with the primary goal of enhancing students' learning independence. Additionally, the effectiveness of using LMS-based teaching materials in promoting learning independence within the Computer Network and Telecommunications Engineering (TJKT) competency program is examined. The research follows a Research and Development (R&D) approach, utilizing the ADDIE development model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. These stages provide a systematic and effective framework for developing LMS-based teaching materials. The participants in this study include teachers and students from SMKN 1, SMKN 3, and SMKN 6 in Bengkulu City. Data collection methods include expert assessments, learner independence questionnaires, and tests. The collected data will be analyzed using statistical techniques such as mean and t-tests, while expert validation will employ a Likert scale. The research findings indicate that the teaching materials developed in this study are suitable for students, and the utilization of LMS-based teaching materials has proven to enhance learner independence.